Jawabanmu

2013-12-18T15:17:56+07:00
2x+3y = 3 
3x- y   = 10  (kali 3)
2x+3y = 3
9x - 3y=30   (jumlahkan)
11 x = 33
     x = 33/11
        = 3
2x+3y = 3
2(3)+3y = 3
 6 + 3y = 3
       3y = 3-6
           = -3
         y = -3/3
           = -1
maka :2x - y = 2(3) - (-1)
                   = 6 + 1
                   = 7
2013-12-18T21:59:43+07:00
2x+3y= 3
3x-y=10

eliminasi
2x + 3y = 3
9x -  3y = 30  +
11x       = 33
x           = 33/11
          x = 3

substitusi x
3x - y = 10
3(3) - y = 10
9 - y = 10
- y = 10 - 9
     = 1
  y = -1